Penurunan Kadar Glukosa Darah dan Hitung Sel Kupffer Tikus Hiperglikemik Setelah Pemberian Dekok Daun Salam (INDONESIAN BAY LEAF DECOCTION COULD LOWER FASTING BLOOD GLUCOSE LEVEL ON HYPERGLYCEMIC RATS AND LOWER KUPFFER CELL COUNT) - ., Yuliana; Widarsa, Tangking (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
Diabetes mellitus (DM) is a metabolic syndrome due to pancreas failure to produce insulin, thereforehyperglycemia is the hallmark of DM. There is hyperglycemia in this disease. In the world, there isaround143 million diabetes mellitus patients. One of the deathcause in diabetes mellitus is chronic liver disease.Herbal medicine is thought to give less side effect than sintetic medicine. A traditional plant that hashypoglicemia property is decoction of Indonesian bay leaves. This study was aimed to study effectivity ofIndonesian bay leaf decoction in decreasing blood glucose level, pancreas and liver hemorrhage scores, andKupffer cell count on alloxan-induced Wistar rats. This Control Group Design used twenty four rats (threemonth old). The rats were divided randomly into four groups, i.e.: control, 1 mL of Indonesian bay leafdecoction (0.9 g/kg body weight (BW)), 2 mL of Indonesian bay leaf decoction (1.8 g/kg BW), and 3 mL ofIndonesian bay leaf decoction (2.7 g /kg BW). After one week adaptation the rats were inducedwithalloxan,then pretest for fasting blood glucose test was examined. Treatment was given for ten days and posttestblood glucose test was done afterwards. At the end of the experiment, all rats were sacrificed to collectpancreas, kidney, and liver. Those organs were stained with hematoxylin eosin. Levelof fasting bloodglucose, hemorrhage score, on pancreas and kidney and Kupffer cell count were analyzed by using Anova.In conclusion, Indonesian bay leaf decoction may lower fasting blood glucose level on hyperglycemic rats aswell as Kupffer cell count significantly, but it is not likely to give significant result in lowering of pancreasand kidney hemorrhage scores.
Keywords: diabetes mellitus, fasting blood glucose, Kupffer cell count, Indonesian bay leaf decoction, alloxan